Academic Staff Perception of the Extent of Politicizing Administration of Universities: Implications for National Development - Edet, Aniefiok Oswald; Asuquo, Michael Ekpenyong; Okon, James Ekpenyong (Richtmann Publishing, 2020)
The aim of this study was to examine academic staff perception of the extent of politicizing administration of universities: Implications for National Development. The study adopted survey research design. The study was guided by two research questions and two research hypotheses. The population of the study was made up of all academic staff in the University of Calabar and Cross River University of Technology, all in Cross River State, Nigeria. Out of the sample size of 430 academic staff used for the study, 250 were males while 180 were females. The instrument for data collection was entitled: â€œAcademic Staff Perception of the Extent of Politicizing Administration of Universities Questionnaire (ASPEPAUQ).â€ Data collected were analyzed using mean and standard deviation for the research questions. While independent t-test was used to test the two hypotheses formulated for the study. From the result of the study, academic staff members were positive in their perception of the extent of politicizing administration of universities. Male and female academic staff did not differ significantly in their rating of the extent of politicizing administration of universities. It was also found that provision of adequate funds, provision of adequate facilities, proper management of available resources, discouragement of ethnicity and improvement in staff physical/social environment were rated as the vital roles of universities administrators in the administration of universities for national development. It was concluded that due process in practice should be maintained and improved upon by the respective universities administrators to ensure equity and for national development to abound.